Orientación normativa en diccionarios monolingües de inglés como lengua extranjera - Bugueño Miranda, Félix; Campos de Borba, Laura (Colombian Applied Linguistics Journal, 2020)
Guidance in language use is an inherent aspect of language learning. Nonetheless, English linguistics has not paid attention to this dimension. Paradoxically, English learner’s dictionaries are characterized by offering evident guidance on language use. In the framework of a research project to compile a dictionary of Brazilian learners’ doubts about the Spanish language, we decided to investigate the English language lexicographic tradition, whose learner’s dictionaries lead substantial advances in foreign language teaching. This paper aimed to analyse how English learner’s dictionaries provide instruction on language use. The methodology consists of the application of a set of formal distinctions based on the opposition between description and prescription, and, subsequently, prescribing a certain language use or forbidding it. Our results show that the English language lexicography applies this whole array of guidance techniques on a particularly efficient and multidimensional way. We could conclude that the description-prescription dichotomy does not sustain itself in English learner’s lexicography. Ultimately, the act of looking for guidance about the English language in use reflects the learner’s inherent desire for instructions.